Enhancing human milk iodine concentration: a data-driven action plan for Latvia - Aumeistere, Līva; Kovada, Ksenija; Driksna, Annamarija; Kozačenko, Jekaterina; Ciproviča, Inga (Frontiers in Nutrition, 2025)
BackgroundIodine deficiency remains a significant public health challenge in Europe. However, there is currently a lack of data on iodine status among lactating women and infants in Latvia.MethodsThis cross-sectional study assessed the impact of maternal diet on iodine concentration in human milk. The data obtained were used as reference points for planning targeted interventions to improve iodine supply. Between October 2024 and April 2025, pooled 24-h human milk samples, 72-h food diaries and questionnaires on anthropometric, sociodemographic characteristics were collected from 55 exclusively breastfeeding women residing in Latvia. Human milk iodine concentration was determined using inductively coupled plasma mass spectrometry, while dietary data were analyzed using the Estonian open-access dietary analysis program NutriData.ResultsHuman milk iodine concentration among participants varied considerably (15.00–291.00 μg L−1) with a median value (86.00 μg L−1) below the level indicating optimal iodine supply for an exclusively breastfed infant (i.e., 150 μg L−1). A significant positive association was observed between maternal iodine intake and human milk iodine concentration (ρ = 0.407, p = 0.002). The participants’ diets lacked iodine-rich sources (i.e., fish, dairy, iodized salt) and, without supplementation, did not reach the adequate intake for iodine (i.e., 200 μg per day).ConclusionPreliminary data indicate that current maternal dietary practices in Latvia are insufficient to guarantee optimal iodine supply to exclusively breastfed infants. Study results highlight the need for policy reforms and improved nutritional guidance to address the iodine deficiency problem in Latvia.